A Qualitative Study of Diversity and Its Management in the Australian Public Service (APS): Employee Perceptions - Soldan, Zhanna; Nankervis, Alan (Common Ground Publishing LLC, 2014)
Over the past two decades, the changing demographics of Australian society and its workforce have forced many APS agencies to proactively engage in diversity efforts. Despite this growing commitment to diversity management (DM), the issues of how employees perceive diversity and its management and their level of support (or lack thereof) for DM have received only modest attention from researchers, particularly in the APS. To obtain an accurate view of diversity and its management, the experience and insight of public sector employees and managers was sought via a qualitative approach, involving case study interviews. The findings reveal that despite the limited awareness of the existence of a workplace diversity plan (WDP) among participants, there was a good level of understanding of the "supposed" objectives of the plan. Diversity was seen to provide considerable advantages both at the functional and the outcome level as well as hallenges, particularly in terms of communication. The perception that women display greater daptability when confronted with diversity, together with the fact that a WDP promises improved career opportunities and more equitable and considerate treatment, largely explain why women were found to be more supportive of WDP than men. Whilst there are signs of improvement in terms of diversity intake and advancement at the lower levels of the organisation, real progress in implementing the ideals through to senior executive service (SES) levels is much slower. The agency’s commitment to DM is viewed as a compliance issue that the federal government has mandated rather than an agency choice. Overall, DM has emerged as a practice with a high value in theory, but with considerable problems to achieve in practice, with the "internal culture" of resistance being the hardest barrier to overcome. The practical mplications of the results for management are discussed; the limitations are noted, along with suggested avenues for future research.